Les échanges féministes franco-italiens par la traduction éditoriale depuis les années 1960 - Fanny Mazzone (Laboratoire Italien)
This paper analyses French and Italian exchanges on the subjects of feminism and gender in the light of French translations of books originally published by specialised publishing houses and collections in Italy. The focus on translation firstly provides a panoramic perspective on feminism, women and gender in Italy and also assesses how specialised publishing affects cultural exchanges through the transfer of these texts. Whilst the publication of a book in a specialised house provides a framework for interpreting it or reinforces its militant message, the transfer from one language to another does not always involve homologous structures. Nonetheless, through their translation, policies, specialised publishers helped to promote the transnational circulation of feminist thought, in languages other than English, through the export of various texts. The development of a new offer—previously unpublished, translated, or rediscovered, of local origin or from elsewhere—reflects the editorial rivalry generated by the opening up of a new market from the activist core, a market which was later populated by better positioned publishers.